Intestinal microbiota regulates naïve lymphocyte migration in Peyer’s patches - Kabbert, Johanna; Kaminski, Anne; Pabst, Oliver; Ugur, Milas (Frontiers in Immunology, 2025)
Peyer’s patches (PPs) are lymphoid organs in the small intestine that serve as inductive sites for both humoral and cellular immune responses against the microbiota, food antigens and pathogens. PPs in germ-free mice are small and hypocellular, highlighting the importance of the microbiota in regulating PP size. However, it is unclear whether this regulation reflects changes in immune cell activation and germinal center responses or alterations in lymphocyte migration kinetics. In this study, we modified the composition and density of the microbiota using antibiotics to investigate the corresponding changes in PP cellularity. We demonstrated that distinct microbiota compositions can result in a reduction in PP size. This reduction was limited to PPs in the distal small intestine, and it reached germ-free levels after only three days of antibiotic treatment. Reduction in PP size was largely due to changes in lymphocyte circulation kinetics in PPs. Lymphocyte egress blockade using the functional S1PR1 antagonist FTY720 prevented the antibiotic-induced decrease in PP cellularity and the entry of naïve lymphocytes into PPs was reduced in antibiotic-treated mice. Our findings uncover a previously unrecognized role for the microbiota in regulating the migration of naïve lymphocytes into PPs, which has implications for the modulation of adaptive immune responses in the intestine.